Perspektif Peran Dinas Sosial Jawa Timur Ditinjau dalam Pemberian Izin Private Adoption - Sheila Puspaningrum (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Direct adoption is the process of adopting a child without the intermediary of a child-rearing institution, carried out by a family or other party. Direct adoption requires certain requirements and steps to obtain permission, as outlined in Minister of Social Affairs Regulation Number 110/HUK/2009 concerning Child Adoption Requirements. The party responsible for granting direct adoption permits in East Java is the East Java Social Services Agency. This study aims to analyze and describe the role of the East Java Social Services Agency in granting direct adoption permits as seen in the Minister of Social Affairs Regulation Number 110/HUK/2009 concerning Child Adoption Requirements. This research method uses descriptive qualitative with a purposive sampling technique for determining informants. The results of the study indicate that two factors, namely the role of the East Java Provincial Social Service as the Regional Child Adoption Permit Consideration Team and as the party acting as the issuer of the child adoption permit, have in principle been implemented effectively and in accordance with applicable regulatory provisions. However, in the aspect of eligibility assessment, especially in fulfilling administrative requirements, more comprehensive optimization is still needed. This is due to the limited detailed information received by applicants regarding the procedures and documents that must be fulfilled, resulting in various difficulties in preparing child adoption documents directly. This condition is feared to impact the results of the eligibility assessment of prospective adoptive parents, considering that incomplete administration often becomes an obstacle in the verification and assessment process which ultimately can influence the final decision regarding granting a child adoption permit.